A novel therapy targeting the gut–liver axis for chronic hepatitis B: Ursodeoxycholic acid plus Bifidobacterium - Zhen Xun; Xiaobao Yao; Caorui Lin; Xinyao Yang; Yanfang Zhang; Xin Yang; Yujue He; Renquan Jiang; Yanping Lan; Yuchen Ye; Detai Ye; Shanjian Chen; et al. (JHEP Reports, 2025)
Background & Aims: Targeting the gut–liver axis is a promising strategy for treating liver diseases. We aimed to assess the therapeutic efficacy of targeting the gut microbiota-bile acid (BA) axis using ursodeoxycholic acid (UDCA) combined with the probiotic Bifidobacterium to treat chronic hepatitis B (CHB). Methods: BA profiles were characterized by mass spectrometry, and gut microbiota composition was analyzed using 16S rRNA sequencing in patients with CHB and healthy controls (HCs). The effects of UDCA and Bifidobacterium were assessed both in a preclinical model and in a 2-month clinical trial involving 22 patients with CHB who received either UDCA (250 mg twice daily; n = 6), Bifidobacterium (2 g twice daily; n = 6), or a combination of UDCA and Bifidobacterium (n = 10). Results: UDCA was the most significantly decreased serum BA in patients with CHB compared to HCs (p <0.001), and had the strongest anti-HBV effect in vitro and in vivo. In the gut, the Bifidobacterium abundance was the most dramatically decreased fecal genus in patients with CHB (p = 0.018), and had the anti-HBV effect in vivo. Finally, combined treatment with UDCA and Bifidobacterium significantly reduced serum alanine aminotransferase (p = 0.008), HBV DNA (77% reduction; p <0.001), pregenomic RNA (59% reduction; p <0.001), and hepatitis B surface antigen (15% reduction; p = 0.002) levels. It also decreased NKG2A expression on natural killer (NK) cells and PD-1 expression on CD8+ T cells by approximately 50% (p <0.01), while enhancing secretion of granzyme B, perforin, and interferon-γ by CD8+ T and NK cells (p <0.05). These effects were superior to those achieved with either monotherapy. Conclusions: Combined treatment with UDCA and Bifidobacterium promotes CD8+ T/NK cell function and viral control in patients withCHB and may represent a promising adjunct therapy warranting further investigation. Impact and implications: Targeting the gut microbiota-bile acid axis has the potential to treat chronic hepatitis B. Results from preclinical models and a clinical trial show that combination treatment with ursodeoxycholic acid plus the probiotic Bifidobacterium exerts antiviral effects in patients with chronic hepatitis B by promoting CD8+ T cell and natural killer cell function. These findings may advance the understanding of HBV immunology and treatment options for chronic hepatitis B. Clinical Trial Number: ChiCTR2200062861.